What Is the Purpose of Learning on the Migrants' Road? - Knežić, Branislava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
Even today, it is evident that the number of migrants over the last few years has struck us. Although good legal regulation of asylum seekers' position, rights, procedures and obligations exists in Serbia, the situation is very different in practice. In other words, these problems can not be approached primarily as security issues of „law and order“ but as a complex problem that requires socio-psychological and cultural-educational support, without which there is no successful integration or socialisation. Police, armed forces, high walls and barbed wire can not stop migrants or resolve newly-formed problems. After crossing borders and borders and travelling for a long time, sometimes more than a year, often exhausted and in poor health and hygienic condition, migrants are often disoriented and do not know that they are stuck in Serbia on their road to salvation. In that difficult situation between hope and fear, they are preoccupied with more urgent problems than education and learning. Although Serbia is not their desired destination, many of them wait for a long time to resolve their fate or to organise their trip to the European Union, where learning, whether formal or informal, may be purposeful and applicable. The answer to the question of what the purpose of migrants' learning is may be different: learning and education are lifelong processes, and they become a necessity for modern humans even when they are on the migrants' road; adaptation to life conditions in a new situation; acquisition of communication skills, etc. Are there organised education and learning on the migrants' road, and how much can they be used as support to adult migrants, are the questions to which we will dedicate the following lines, and easily show to ourselves and to readers that we write about something that is not even known, that is unknown.